Reproducibility of an organoleptic method for halitosis assessment - de Mesquita-Guimarães, Késsia Suênia Fidelis; Santin, Gabriela Cristina; Scatena, Camila; Rodrigues, Antônio Luiz, Junior; Serra, Mônica Campos (European Journal of General Dentistry, 2017)
Background: The organoleptic evaluation is considered the gold standard between evaluation methods of halitosis, but its main drawback is the difficulty of reproducibility. Purpose: The aim of this study was to evaluate the reproducibility of an organoleptic evaluation method using three levels of scores (0 = no odor, 1 = moderate odor, and 2 = strong odor) to increase reliability between researchers and clinicians. Methods: The evaluation was blindly conducted by two examiners previously calibrated by the Smell Identification Test and compliance in clinical trials. Statistical calculations were done with STATA ® software version 9.0. Results: The degree of agreement between examiners was 82.5%, with estimated Kappa (κ=0.69), with substantial agreement. Conclusion: The scale used in this study by organoleptic method was effective and reproducible but must be repeated and compared to other methods for better consistency of results.
Keywords: Breath; halitosis; judges; organoleptic